Fenomenologia – wprowadzenie w lekturę tekstu Edmunda Husserla „Phänomenologie (Der Encyclopaedia Britannica Artikel)” - Bekrycht, Tomasz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2015)
The article presents in the synthetic way the major assumptions of phenomenology as the philosophical movement. The author has delineated two tasks. Firstly, introduction to the major issues of phenomenology and underlining important origins of phenomenology, i.e. Edmund Husserl’s work – Logical Investigations. Secondly, introduction to the reading of an important text (unpublished in Polish by now) that describes the basic foundations of this phenomenological movement, which have been developed by its creator.
Phenomenology – introduction to reading text: „Der Encyclopaedia Britannica Artikel” (Phänomenologie)
Keywords: phenomenology; ontology; transcendental philosophy; phenomenological reduction; Edmund Husserl; Martin Heidegger